2013
DOI: 10.1002/net.21527
|View full text |Cite
|
Sign up to set email alerts
|

Forty years of periodic vehicle routing

Abstract: The periodic vehicle routing problem (PVRP) first appeared in 1974 in a paper about garbage collection (Beltrami and Bodin, Networks 4 (1974), 65–74). The wide applicability and versatility of the problem has led to a vast body of literature addressing both novel applications and solution methods. This article discusses the wide array of circumstances and settings in which the PVRP has been applied and describes the development of solution methods, both exact and heuristic, for the PVRP. As with many core rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(67 citation statements)
references
References 79 publications
0
64
0
3
Order By: Relevance
“…In recent years, its variants have grown ever more popular in the literature (as discussed by Gendreau et al (2005a,b); Eksioglu et al [106]; Braekers et al [107]), though current models vary widely as more and more researchers aim to enable their models to cope with real-life complexities and the literature on vehicle routing problems has been growing exponentially at a rate of 6% each year [106,107] and many surveys focused on specific variants can be observed as well [108][109][110][111][112][113][114][115][116][117][118][119]. In general, the classical vehicle routing problem can be defined on a graph = ( , ), where = {0, 1, .…”
Section: Vrpmentioning
confidence: 99%
“…In recent years, its variants have grown ever more popular in the literature (as discussed by Gendreau et al (2005a,b); Eksioglu et al [106]; Braekers et al [107]), though current models vary widely as more and more researchers aim to enable their models to cope with real-life complexities and the literature on vehicle routing problems has been growing exponentially at a rate of 6% each year [106,107] and many surveys focused on specific variants can be observed as well [108][109][110][111][112][113][114][115][116][117][118][119]. In general, the classical vehicle routing problem can be defined on a graph = ( , ), where = {0, 1, .…”
Section: Vrpmentioning
confidence: 99%
“…The PVRP is first proposed by Beltrami and Bodin (1974) to route and schedule periodic collection of municipal waste in one of the earliest papers applying vehicle routing to waste collection. Reviews of the PVRP literature can be found in Francis et al (2008) and Campbell and Wilson (2014). The LRP is the single-period version of the PLRP.…”
Section: Related Modeling Literaturementioning
confidence: 99%
“…In these applications operators correspond to vehicles and tours have to be built such that no stock-outs occur at the retailers and the routing and inventory costs are minimal. Some examples are mentioned in Campbell and Wilson (2014) and Coelho et al (2013). The operator costs resemble costs for vehicle usage and the service request costs can model inventory costs.…”
Section: Practical Applications and Related Literaturementioning
confidence: 99%